Pelatihan Pelatihan Pengembangan Modul Ajar Berbasis Kurikulum Merdeka Bagi Guru SMK Produktif Kota Makassar: Indonesia - Muhammad Yahya; Sidin, Udin Sidik; Wahyudi (Jurusan Teknik Informatika dan Komputer, 2023)
The Independent Curriculum-based Teaching Module Development Training is an initiative directed at strengthening the pedagogical skills of Productive Vocational High School (SMK) teachers in Makassar City. The Merdeka Curriculum gives schools the freedom to develop teaching modules that are relevant to local and industry needs. This research aims to improve the quality of teaching and learning in Productive Vocational Schools through this training. The training method involves Productive SMK teachers in the process of developing teaching modules. The activity begins with an in-depth understanding of the essence of Merdeka Curriculum and the specific needs of students of Productive Vocational Schools in Makassar City. Furthermore, trainees are provided with guidance and skills in designing teaching modules that are responsive to the local context and incorporate applicable curriculum principles. Training results are measured through qualitative and quantitative assessments of the teaching modules produced. In addition, a participatory evaluation was conducted involving teachers, students, and industry as key stakeholders. It was found that this training was effective in increasing teachers' understanding of the Merdeka Curriculum and was able to produce teaching modules that were more contextual and relevant. The conclusion of this activity is that training in developing teaching modules based on the Merdeka Curriculum can be a strategic step in improving the quality of education in Productive Vocational Schools. By involving teachers in the module development process, they can better understand student needs and produce teaching materials that are more in line with the demands of the industrial world. The implications of this research can provide guidance for education policy at the regional level in supporting the implementation of the Merdeka Curriculum in Productive SMK schools.